L: A Review Study With an Antioxidant Prospective - Sepide Miraj PhD; Rafieian-Kopaei PhD; Sara Kiani (SAGE Publishing, 2017)
Melissa officinalis is a plant cultivated in some parts of Iran. The leaves of lemon balm, Melissa officinalis L (Lamiaceae), are used in Iranian folk medicine for their digestive, carminative, antispasmodic, sedative, analgesic, tonic, and diuretic properties, as well as for functional gastrointestinal disorders. This review article was aimed not only to introduce Melissa officinalis (its growth condition, its chemical compounds, and its traditional usages) but also to overview its antioxidant properties in detail. This review was carried out by searching studies in PubMed, Medline, Web of Science, and IranMedex databases up to 2016. The search terms used were " Melissa officinalis L," "antioxidant properties," oxidative stress," "oxidative damage", "ROS." Articles whose full texts were not available were excluded from the study. In this study, firstly, traditional usage of this herb was reviewed, including antimicrobial activity (antiparasitic, antibacterial, antiviral, etc), antispasmodic, and insomnia properties. Then, its antioxidant properties were overviewed. Various studies have shown that Melissa officinalis L possesses high amount of antioxidant activity through its chemical compounds including high amount of flavonoids, rosmaric acid, gallic acid, phenolic contents. Many studies confirmed the antioxidative effects of Melissa officinalis ; thus, its effect in preventing and treating oxidative stress-related diseases might be reliable.